Full-Range Public Health Leadership, Part 1: Quantitative Analysis - Carlton, Erik L.; Holsinger, James W.; Riddell, Martha; Bush, Heather (Frontiers in Public Health, 2015)
Background Workforce and leadership development are central to the future of public health. However, public health has been slow to translate and apply leadership models from other professions and to incorporate local perspectives in understanding public health leadership. Purpose This study utilized the full-range leadership model in order to examine public health leadership. Specifically, it sought to measure leadership styles among local health department directors and to understand the context of leadership in local health departments. Methods Leadership styles among local health department directors (n = 13) were examined using survey methodology. Quantitative analysis methods included descriptive statistics, boxplots, and Pearson bivariate correlations using SPSS v18.0. Findings Self-reported leadership styles were highly correlated to leadership outcomes at the organizational level. However, they were not related to county health rankings. Results suggest the preeminence of leader behaviors and providing individual consideration to staff as compared to idealized attributes of leaders, intellectual stimulation, or inspirational motivation. Implications Holistic leadership assessment instruments such as the multifactor leadership questionnaire can be useful in assessing public health leaders’ approaches and outcomes. Comprehensive, 360-degree reviews may be especially helpful. Further research is needed to examine the effectiveness of public health leadership development models, as well as the extent that public health leadership impacts public health outcomes.